Principles of Finance - Julie R. Dahlquist; Rainford Knight (OpenStax, 2022)
Designed to meet the scope and sequence of your course, Principles of Finance provides a strong foundation in financial applications using an innovative use-case approach to explore their role in business decision-making. An array of financial calculator and downloadable Microsoft Excel data exercises also engage students in experiential learning throughout. With flexible integration of technical instruction and data, this title prepares students for current practice and continual evolution.
Keywords: 330; Finance